Resist material and pattern forming method

The resist material with a polymer, vinyl ether crosslinking agent, and thermal acid generator addresses crosslinking inefficiencies and storage stability issues, providing improved edge roughness and resolution for fine pattern formation in semiconductor manufacturing.

JP7605783B2Active Publication Date: 2024-12-24SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022042937
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2024-12-24
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Conventional resist materials face issues with insufficient crosslinking reactions during short-time baking, leading to unreacted crosslinking agents, storage stability problems, and increased edge roughness and dimensional variations due to acetal structure decomposition by strong acids, affecting lithography performance.

Method used

A resist material comprising a polymer with hydroxyl or carboxy groups, a vinyl ether crosslinking agent, a thermal acid generator, and a quencher, which promotes efficient crosslinking on the substrate while maintaining storage stability, using a weak acid generator to control the crosslinking reaction.

Benefits of technology

The resist material achieves small edge roughness, excellent resolution, and good pattern shape with improved storage stability, suitable for fine pattern formation in photomasks and semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605783000077
    Figure 0007605783000077
  • Figure 0007605783000001
    Figure 0007605783000001
  • Figure 0007605783000002
    Figure 0007605783000002
Patent Text Reader

Abstract

To provide a resist material having small edge roughness and dimensional variations and having a good pattern shape after exposure, and to provide a pattern forming method.SOLUTION: The resist material contains: (Ia) a polymer which contains a repeating unit (A) containing a hydroxyl group or a carboxy group; (II) a crosslinking agent having a structure represented by formula (1); (III) a thermal acid generator having a structure represented by formula (2); (IV) an organic solvent; and (V) a component which is decomposed by irradiation with active rays or radiation to generate an acid.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resist material and a pattern forming method. [Background technology]

[0002] As LSIs become more highly integrated and faster, pattern rules are becoming finer at a rapid pace. This is because 5G high-speed communications and artificial intelligence (AI) are becoming more widespread, and high-performance devices are needed to process these. The most advanced miniaturization technology is extreme ultraviolet (EUV) lithography with a wavelength of 13.5 nm, which is used to mass-produce 5 nm node devices. Furthermore, studies are underway to use EUV lithography for next-generation 3 nm node devices and the next-next generation 2 nm node devices.

[0003] In lithography using DUV light sources, i.e. KrF and ArF excimer lasers, chemically amplified resists, which change the solubility in the developer by reacting the base polymer resin with the acid generated from the photosensitive agent upon exposure as a catalyst, have achieved high-sensitivity, high-resolution lithography and have led the advancement of miniaturization as the main resist used in actual production processes.

[0004] Chemically amplified resists continue to be widely studied for next-generation lithography such as EUV, and have been commercialized. Meanwhile, the demand for improved resist performance is increasing as the device becomes finer. In particular, the variation in resist pattern dimensions (line edge roughness: LER) affects the variation in pattern dimensions after substrate processing, and ultimately affects the operational stability of the device, so it is necessary to suppress this to the utmost.

[0005] There are various factors that can be considered as factors of LER in chemically amplified resists, such as the characteristics of the dissolution rate change curve (dissolution contrast) versus exposure dose, acid diffusion length, compatibility of mixed compositions, etc. In addition, the influence of the chain length, molecular size, and molecular weight of the polymer resin has recently been attracting attention. It is thought that reducing the molecular weight of the polymer to reduce the dissolution unit during development is effective in reducing LER.

[0006] However, as the molecular weight of the base polymer decreases, problems such as pattern collapse due to a decrease in strength, promotion of acid diffusion due to a drop in the glass transition temperature (Tg), and a decrease in resolution due to an increase in the solubility of the developer in the unexposed area may occur. In order to solve these problems, attempts have been made to crosslink polymer chains with an acid-decomposable crosslinking group. The molecular weight can be increased in advance by crosslinking, and the crosslinks in the exposed area can be decomposed by the acid generated during exposure. Patent Document 1 discloses a crosslinked polymer obtained by reacting a unit having a carboxyl group or a hydroxyl group with a divinyl ether unit.

[0007] On the other hand, the crosslinked polymer generated by crosslinking between polymer chains has a very large molecular weight, and when stored for a long period of time as a resist solution, the polymers tend to aggregate, causing an increase in the number of defects.

[0008] Patent Document 2 discloses a resist material containing a polymer having a reactive site and a monomer crosslinking agent.

[0009] Furthermore, Patent Document 3 discloses a positive-type heat-sensitive resist material that contains a polymer having a reactive site, a monomer crosslinking agent, and a thermal acid generator to bring about intramolecular crosslinking.

[0010] However, in the baking process after coating on a substrate, the crosslinking reaction between the crosslinker and the polymer does not proceed sufficiently, and the remaining monomeric components have a negative effect on lithography performance. In addition, when the acid generated in the exposed area by the action of the photoacid generator diffuses to the unexposed area, the crosslinked structure is easily decomposed. In addition, adding an acid to the resist solution for the purpose of promoting the crosslinking reaction causes problems in storage stability, such as fluctuations in film thickness, because the crosslinking reaction proceeds during storage of the solution. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Patent No. 5562651 [Patent Document 2] International Publication No. WO2018 / 079449 [Patent Document 3] Patent Publication No. 2000-187326 Summary of the Invention [Problem to be solved by the invention]

[0012] In resists containing a compound having a vinyl ether group as a crosslinking agent, an acetal structure is formed by an addition reaction with a carboxyl group or a hydroxyl group. On the other hand, the acetal structure formed is easily decomposed by the action of a strong acid component generated from a photoacid generator, so that the resist film has a low molecular weight in the exposed area and a high molecular weight in the unexposed area, and the dissolution contrast can be increased.

[0013] However, in the conventional resist containing a crosslinking agent, the crosslinking reaction does not proceed sufficiently in a short baking process, and the crosslinking agent remains unreacted. In addition, since the acetal structure is very easily decomposed, it easily decomposes to generate a monomer component due to the diffusion of a strong acid component generated in the exposed area. Such components have a plasticizer-like effect in the resist film and lower the glass transition point of the film, which promotes the diffusion of the acid generated by exposure and leads to a deterioration in lithography performance. In addition, adding an acid to a resist solution for the purpose of promoting the crosslinking reaction causes a problem in storage stability due to the progression of an undesired crosslinking reaction during storage of the solution.

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a resist material and a pattern formation method which have sensitivity, resolution, and dissolution contrast superior to conventional positive resist materials, and which have small edge roughness and dimensional variation and produce a good pattern shape after exposure. [Means for solving the problem]

[0015] In order to solve the above problems, the present invention provides A resist material comprising: (Ia) a polymer containing a repeating unit (A) containing a hydroxyl group or a carboxyl group; (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; (V) a component that decomposes when exposed to actinic rays or radiation to generate an acid; and A resist material comprising to provide. [ka] In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group. n is an integer of 1 to 4. [ka] [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

[0016] Such a resist material can provide a resist material that exhibits small edge roughness and dimensional variation after exposure, has excellent resolution, produces a good pattern shape after exposure, and also has good storage stability.

[0017] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A resist material comprising: (Ib) a polymer containing a repeating unit (A) having a hydroxyl group or a carboxyl group, and a repeating unit (C) having a structural moiety that is decomposed upon exposure to actinic rays or radiation to generate an acid, (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; A resist material comprising to provide. [ka] In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group. n is an integer of 1 to 4. [ka] [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

[0018] Such a resist material can provide a resist material that exhibits small edge roughness and dimensional variation after exposure, has excellent resolution, produces a good pattern shape after exposure, and also has good storage stability.

[0019] The repeating unit (C) contained in the polymer is preferably represented by the following formula (c). [ka] [In the formula, R c1 is a hydrogen atom or a methyl group. Z 1 is a single bond or an ester bond. 2 is a single bond or a divalent organic group having 1 to 25 carbon atoms, and may contain one or more of an ester bond, an ether bond, a lactone ring, an amide bond, a sultone ring, and an iodine atom. Rf c1 ~Rf c4 are each independently a hydrogen atom, a fluorine atom, or a trifluoromethyl group, provided that at least one of them is a fluorine atom or a trifluoromethyl group. R c2 ~R c4 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may contain a heteroatom, and R c2 , R c3 and R c4Any two of may be bonded to each other to form a ring together with the sulfur atom to which they are attached.

[0020] Such a resist material can provide a resist material that has good solubility in an alkaline developer.

[0021] The resist material preferably further contains (V) a component that decomposes upon irradiation with actinic rays or radiation to generate an acid.

[0022] Such a resist material can improve the dissolution contrast with the unexposed area.

[0023] The repeating unit (A) contained in the polymer is preferably represented by the following formula (a1) and / or (a2). [ka] [In the formula, R A Each of Y is independently a hydrogen atom or a methyl group. a1 Y each independently represents a single bond or a divalent linking group having 1 to 15 carbon atoms and having at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom. a2 R are each independently a single bond or a divalent linking group having 1 to 12 carbon atoms and at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom. a1 is a hydrogen atom, a fluorine atom, or an alkyl group; R a1 and Y a2 may be bonded to form a ring. k is 1 or 2, l is an integer of 0 to 4, and 1≦k+l≦5. m is 0 or 1.]

[0024] Such a resist material can suppress the diffusion of acid generated in exposed areas by the action of a photoacid generator.

[0025] In addition, R in the formula (2)31 Preferably, contains an iodine atom.

[0026] Such a resist material can promote the crosslinking reaction of the polymer in the resist material on the substrate.

[0027] Moreover, R in the formula (1) preferably contains an aromatic hydrocarbon group.

[0028] Such a resist material can improve the contrast between exposed and unexposed areas.

[0029] Moreover, the resist material preferably further contains a quencher (VI).

[0030] Such a resist material can suppress the diffusion of acid generated in exposed areas by the action of a photoacid generator.

[0031] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A pattern formation method comprising the steps of: (i) applying the resist material onto a substrate to form a resist film; (ii) exposing the resist film to high energy radiation; (iii) developing the exposed resist film using a developer; The present invention provides a pattern forming method comprising the steps of:

[0032] Such a pattern forming method can provide a pattern with small edge roughness and dimensional variation, excellent resolution, and a good pattern shape after exposure.

[0033] Moreover, the step (i) preferably further comprises a step of pre-baking the resist film at 130° C. or higher.

[0034] Such a pattern formation method allows the crosslinking reaction caused by the crosslinking agent to proceed efficiently. Effect of the Invention

[0035] The resist material of the present invention contains a polymer having a reactive group, a vinyl ether crosslinking agent, and a thermal acid generator of ammonium carboxylate type. This thermal acid generator generates a weak acid by heating in the baking process, and promotes the crosslinking reaction. The generated fluorocarboxylic acid has an acidity suitable for promoting the crosslinking reaction. On the other hand, since the thermal acid generator is a weak acid salt, even if it is added to the resist solution, it does not cause an undesired crosslinking reaction during storage of the solution, and therefore the problem of storage stability is also solved.

[0036] Furthermore, when the resist material contains a quencher component, the effect of the quencher component is such that a neutral environment is maintained in the solution state while a weakly acidic environment is maintained in the minute exposed areas, thereby trapping the acid generated in the exposed areas and further suppressing the diffusion of the acid.

[0037] The resist material of the present invention, which contains a specific thermal acid generator and a vinyl ether crosslinking agent, efficiently progresses the crosslinking reaction of polymer chains due to the above-mentioned effects, and has excellent pattern shape, roughness, and resolution after exposure, and good storage stability, making it highly practical, and particularly useful as a fine pattern forming material for photomasks for VLSI manufacturing or EB drawing, and a pattern forming material for EB or EUV lithography. The resist material of the present invention can be applied, for example, not only to lithography in semiconductor circuit formation, but also to the formation of mask circuit patterns, micromachines, and thin-film magnetic head circuits. [Brief description of the drawings]

[0038] [Figure 1] 1 is a graph comparing contrast between an embodiment of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] As described above, there has been a demand for the development of a resist material which exhibits small edge roughness and dimensional variation, excellent resolution, favorable pattern shape after exposure, and also favorable storage stability.

[0040] As a result of extensive investigations aimed at solving the above-mentioned problems, the present inventors have completed the present invention, which enables the formation of patterns with small LER and excellent resolution in a resist containing a polymer compound having a specific functional group, a specific vinyl ether crosslinking agent, and a specific carboxylate-type thermal acid generator, and which overcomes the problem of storage stability.

[0041] That is, the first aspect of the present invention is A resist material comprising: (Ia) a polymer containing a repeating unit (A) containing a hydroxyl group or a carboxyl group; (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; (V) a component that decomposes when exposed to actinic rays or radiation to generate an acid; and The resist material is characterized by comprising: [ka] In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group. n is an integer of 1 to 4. [ka] [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R33 and R 34 Any two of may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

[0042] In addition, the second aspect of the present invention is A resist material comprising: (Ib) a polymer containing a repeating unit (A) having a hydroxyl group or a carboxyl group, and a repeating unit (C) having a structural moiety that is decomposed upon exposure to actinic rays or radiation to generate an acid, (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; The resist material is characterized by comprising: [ka] In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group. n is an integer of 1 to 4. [ka] [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

[0043] The present invention will be described in detail below, but the present invention is not limited thereto.

[0044] [First aspect] A first aspect of the present invention is a resist material containing the above-mentioned components (Ia), (II), (III), (IV) and (V). Each component will be described in detail below.

[0045] [(Ia) Base polymer] The base polymer (P) in the present invention contains a repeating unit (A) containing a hydroxyl group or a carboxyl group. The repeating unit (A) functions as a reaction site with the crosslinking agent (II) described below, and forms a polymer on the substrate, thereby making it possible to suppress the diffusion of acid generated in exposed areas by the action of a photoacid generator.

[0046] The repeating unit (A) is preferably one represented by the following formula (a1) or (a2). [ka]

[0047] In formulas (a1) and (a2), R A are each independently a hydrogen atom or a methyl group.

[0048] In formula (a1), Y a1 are each independently a single bond or a divalent linking group having 1 to 15 carbon atoms and having at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom.

[0049] In formula (a2), Y a2 each independently represents a single bond or a divalent linking group having 1 to 12 carbon atoms and having at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom.

[0050] In formula (a2), R a1 is a hydrogen atom, a fluorine atom, or an alkyl group; R a1 and Y a2 may be bonded to form a ring.

[0051] In formula (a2), k is 1 or 2. l is an integer of 0 to 4, provided that 1≦k+l≦5. m is an integer of 0 or 1.

[0052] Examples of monomers that provide the repeating unit (a1) include, but are not limited to, those shown below. [ka]

[0053] Examples of monomers that provide the repeating unit (a2) include, but are not limited to, those shown below. [ka]

[0054] The content of the repeating unit (A) in the base polymer (P) is preferably 5 mol % or more, and more preferably 10 mol % or more and 80 mol % or less.

[0055] As the repeating unit (A), repeating units other than the repeating units (a1) and (a2) can also be used.

[0056] The base polymer (P) preferably further contains a repeating unit (B) in which the hydrogen atom of the carboxyl group in the repeating unit (A) is replaced with an acid labile group. The main methods for changing the solubility of the resist film in the developer include changing the molecular weight and changing the polarity. The crosslinking agent (II) acts to change the molecular weight, and the repeating unit (B) changes the polarity, so that the contrast can be significantly improved.

[0057] The repeating unit (B) is preferably represented by the following formula (b). [ka]

[0058] In formula (b), R b is a hydrogen atom or a methyl group. b R is a divalent linking group having 1 to 15 carbon atoms and at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom. b1 is an acid labile group.

[0059] Examples of monomers that provide the repeating unit (b) include, but are not limited to, those shown below. [ka]

[0060] [ka]

[0061] Also, R b1 Examples of the acid labile group represented by the formula (AL-3)-1 to (AL-3)-19 below can be mentioned, but are not limited to these. [ka] (In the formula, the dashed lines represent bonds.)

[0062] In formulas (AL-3)-1 to (AL-3)-19, R L14 R are each independently a saturated hydrocarbyl group having 1 to 8 carbon atoms or an aryl group having 6 to 20 carbon atoms. L15 and R L17 R are each independently a hydrogen atom or a saturated hydrocarbyl group having 1 to 20 carbon atoms. L16 R is an aryl group having 6 to 20 carbon atoms. The saturated hydrocarbyl group may be linear, branched, or cyclic. The aryl group is preferably a phenyl group. F is a fluorine atom or a trifluoromethyl group, and g is an integer of 1 to 5.

[0063] The content of the repeating unit (B) in the base polymer (P) is preferably 90 mol % or less, and more preferably 70 mol % or less and 20 mol % or more.

[0064] [(II) Crosslinking agent] The crosslinking agent (II) in the present invention has a vinyl ether group that undergoes an addition reaction with a carboxyl group or a hydroxyl group of the structural unit (A) of the base polymer (P). By crosslinking the base polymers together on the substrate, the molecular weight is significantly increased, and the diffusion of the acid and dissolution in the developer are suppressed. In addition, the acetal structure formed after the crosslinking reaction is decomposed by a strong acid component generated from the component (V) that generates an acid upon exposure to be described later, and only the exposed portion has a low molecular weight, thereby improving the contrast between the exposed portion and the unexposed portion.

[0065] The crosslinking agent (II) has a structure represented by the following formula (1). [ka]

[0066] In formula (1), L 1 is a linking group selected from a single bond, an ester bond, and an ether bond.

[0067] In formula (1), R 1 is a single bond or a divalent organic group.

[0068] In formula (1), R is an n-valent organic group which may have a substituent. R preferably contains a cyclic structure, and more preferably the cyclic structure is an aromatic hydrocarbon group.

[0069] In formula (1), n ​​is an integer of 1 to 4. It is preferable that n is 2 or more.

[0070] Examples of the crosslinking agent (II) include, but are not limited to, the following: [ka]

[0071] [ka]

[0072] The content of the crosslinking agent (II) is preferably 0.1 to 50 parts by mass, more preferably 1 to 40 parts by mass, based on 100 parts by mass of the base polymer. The crosslinking agent (II) may be used alone or in combination of two or more kinds.

[0073] [(III) Thermal acid generator] The thermal acid generator (III) in the present invention is a component that accelerates the crosslinking reaction by the acid generated in the baking step.

[0074] The thermal acid generator (III) is a weak acid salt consisting of a carboxylate anion and an ammonium cation. The acid generated in the system promotes the crosslinking reaction but does not contribute to the decomposition of the formed acetal bond.

[0075] The thermal acid generator (III) has a structure represented by the following formula (2). [ka]

[0076] In formula (2), R 31 R is a monovalent organic group which may have a heteroatom or a substituent. The organic group may have an ether bond, an ester bond, an amide bond, a lactone ring, or a sultone ring. 31 Preferably, the alkyl group contains an aromatic hydrocarbon group, and more preferably, the alkyl group contains an iodine atom.

[0077] In formula (2), R 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

[0078] Examples of the anion structure of the thermal acid generator (III) include, but are not limited to, those shown below. [ka]

[0079] [ka]

[0080] [ka]

[0081] [ka]

[0082] Examples of the cation structure of the thermal acid generator (III) include, but are not limited to, those shown below. [ka]

[0083] The content of the thermal acid generator (III) in the resist material of the present invention is preferably 0.1 to 50 parts by mass, more preferably 1 to 40 parts by mass, based on 100 parts by mass of the base polymer (P). The thermal acid generator (III) may be used alone or in combination of two or more kinds.

[0084] [(IV) Organic solvent] The resist material of the present invention contains an organic solvent. The organic solvent is not particularly limited as long as it can dissolve each component contained in the resist material of the present invention. Examples of the organic solvent include ketones such as cyclohexanone, cyclopentanone, methyl-2-n-pentyl ketone, and 2-heptanone, as described in paragraphs

[0144] to

[0145] of JP-A-2008-111103; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and diacetone alcohol; propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, and ethylene glycol Examples of the monoethyl ether include ethers such as propylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate; and lactones such as γ-butyrolactone.

[0085] In the resist material of the present invention, the content of the organic solvent is preferably 100 to 10,000 parts by mass, more preferably 200 to 8,000 parts by mass, based on 100 parts by mass of the base polymer. The organic solvent may be used alone or in combination of two or more kinds.

[0086] [(V) Components that decompose when exposed to actinic rays or radiation to generate an acid] The resist material of the present invention further contains a photoacid generator. The acid generated from the photoacid generator by patternwise exposure is a strong acid with a stronger acidity than the quencher (VI) described below, and decomposes the acid labile group of the repeating unit (B) and the acetal bond formed by the crosslinker (II). This causes a change in polarity and a decrease in molecular weight in the exposed areas of the resist film, improving the dissolution contrast with the unexposed areas.

[0087] The photoacid generator may be, for example, a compound that generates an acid in response to actinic rays or radiation. The photoacid generator may be any compound that generates an acid when irradiated with high-energy rays, but is preferably one that generates a sulfonic acid, an imide acid, or a methide acid. Suitable photoacid generators include sulfonium salts, iodonium salts, sulfonyldiazomethane, N-sulfonyloxyimide, and oxime-O-sulfonate-type acid generators. Specific examples of photoacid generators include those described in paragraphs

[0122] to

[0142] of JP2008-111103A.

[0088] The content of the photoacid generator (V) in the resist material of the present invention is preferably 0.1 to 50 parts by mass, more preferably 1 to 40 parts by mass, based on 100 parts by mass of the base polymer (P). The photoacid generator (V) may be used alone or in combination of two or more kinds.

[0089] As the photoacid generator, a sulfonium salt represented by the following formula (3) can be suitably used. [ka]

[0090] In formula (3), R 21 ~R 23 are each independently a hydrocarbyl group having 1 to 20 carbon atoms which may contain a halogen atom or a heteroatom. The hydrocarbyl group may be linear, branched or cyclic. Specific examples thereof include R c2 ~R c4Examples of the hydrogen atom include the same as those exemplified in the description of R. In addition, some or all of the hydrogen atoms of these groups may be substituted with a group containing a heteroatom such as an oxygen atom, a sulfur atom, a nitrogen atom, or a halogen atom, and some of the -CH2- of these groups may be substituted with a group containing a heteroatom such as an oxygen atom, a sulfur atom, or a nitrogen atom, and as a result, the group may contain a hydroxy group, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, a nitro group, a carbonyl group, an ether bond, an ester bond, a sulfonate ester bond, a carbonate bond, a lactone ring, a sultone ring, a carboxylic acid anhydride, a haloalkyl group, or the like. 21 and R 22 and may be bonded to each other to form a ring together with the sulfur atom to which they are bonded. In this case, the ring is as defined in the explanation of formula (c) as R c2 , R c3 and R c4 Examples of the ring that can be formed by combining any two of the above with the sulfur atom to which they are attached include the same as those exemplified above.

[0091] Examples of the cation of the sulfonium salt represented by formula (3) include the same as those exemplified as the sulfonium cation of the monomer that gives the repeating unit (C) described below.

[0092] In formula (3), Xa - is an anion selected from the following formulas (3A) to (3D). [ka]

[0093] In formula (3A), R fa is a hydrocarbyl group having 1 to 40 carbon atoms which may contain a fluorine atom or a heteroatom. The hydrocarbyl group may be saturated or unsaturated, and may be linear, branched, or cyclic. Specific examples thereof include R 111 Examples of the hydrocarbyl group represented by the formula (I) include the same as those exemplified above.

[0094] The anion represented by formula (3A) is preferably one represented by the following formula (3A'). [ka]

[0095] In formula (3A'), R HF R is a hydrogen atom or a trifluoromethyl group, preferably a trifluoromethyl group. 111 is a hydrocarbyl group having 1 to 38 carbon atoms which may contain a heteroatom. The heteroatom is preferably an oxygen atom, a nitrogen atom, a sulfur atom, a halogen atom, etc., and more preferably an oxygen atom. In order to obtain high resolution in the formation of a fine pattern, the hydrocarbyl group is preferably one having 6 to 30 carbon atoms.

[0096] R 111 The hydrocarbyl group represented by the formula (I) may be saturated or unsaturated, and may be linear, branched or cyclic. Specific examples thereof include alkyl groups having 1 to 38 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a neopentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, a nonyl group, an undecyl group, a tridecyl group, a pentadecyl group, a heptadecyl group, and an icosanyl group; a cyclopentyl group, a cyclohexyl group, a 1-adamantyl group, a 2-adamantyl group, a 1-adamantylmethyl group, and a norbornyl group. cyclic saturated hydrocarbyl groups having 3 to 38 carbon atoms, such as a norbornylmethyl group, a tricyclodecanyl group, a tetracyclododecanyl group, a tetracyclododecanylmethyl group, or a dicyclohexylmethyl group; unsaturated aliphatic hydrocarbyl groups having 2 to 38 carbon atoms, such as an allyl group or a 3-cyclohexenyl group; aryl groups having 6 to 38 carbon atoms, such as a phenyl group, a 1-naphthyl group, or a 2-naphthyl group; aralkyl groups having 7 to 38 carbon atoms, such as a benzyl group or a diphenylmethyl group; and groups obtained by combining these.

[0097] In addition, some or all of the hydrogen atoms of these groups may be substituted with groups containing heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, and halogen atoms, and some of the -CH2- of these groups may be substituted with groups containing heteroatoms such as oxygen atoms, sulfur atoms, and nitrogen atoms, resulting in the group containing a hydroxyl group, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, a nitro group, a carbonyl group, an ether bond, an ester bond, a sulfonate ester bond, a carbonate bond, a lactone ring, a sultone ring, a carboxylic acid anhydride, a haloalkyl group, etc. Examples of hydrocarbyl groups containing heteroatoms include a tetrahydrofuryl group, a methoxymethyl group, an ethoxymethyl group, a methylthiomethyl group, an acetamidomethyl group, a trifluoroethyl group, a (2-methoxyethoxy)methyl group, an acetoxymethyl group, a 2-carboxy-1-cyclohexyl group, a 2-oxopropyl group, a 4-oxo-1-adamantyl group, and a 3-oxocyclohexyl group.

[0098] Synthesis of sulfonium salts containing an anion represented by formula (3A') is described in detail in JP-A-2007-145797, JP-A-2008-106045, JP-A-2009-7327, JP-A-2009-258695, etc. In addition, sulfonium salts described in JP-A-2010-215608, JP-A-2012-41320, JP-A-2012-106986, JP-A-2012-153644, etc. are also preferably used.

[0099] Examples of the anion represented by formula (3A) include the same anions as those exemplified as the anion represented by formula (1A) in JP 2018-197853 A.

[0100] In formula (3B), R fb1 and R fb2 are each independently a hydrocarbyl group having 1 to 40 carbon atoms which may contain a fluorine atom or a heteroatom. The hydrocarbyl group may be saturated or unsaturated, and may be linear, branched, or cyclic. Specific examples thereof include R 111Examples of the hydrocarbyl group represented by the formula R include the same as those exemplified above. fb1 and R fb2 is preferably a fluorine atom or a linear fluorinated alkyl group having 1 to 4 carbon atoms. fb1 and R fb2 means that the groups (-CF2-SO2-N - -SO2-CF2-) may form a ring, in which case, R fb1 and R fb2 The group obtained by bonding together is preferably a fluorinated ethylene group or a fluorinated propylene group.

[0101] In formula (3C), R fc1 , R fc2 and R fc3 are each independently a hydrocarbyl group having 1 to 40 carbon atoms which may contain a fluorine atom or a heteroatom. The hydrocarbyl group may be saturated or unsaturated, and may be linear, branched, or cyclic. Specific examples thereof include R 111 Examples of the hydrocarbyl group represented by the formula R include the same as those exemplified above. fc1 , R fc2 and R fc3 is preferably a fluorine atom or a linear fluorinated alkyl group having 1 to 4 carbon atoms. fc1 and R fc2 means that the groups (-CF2-SO2-C - -SO2-CF2-) may form a ring, in which case, R fc1 and R fc2 The group obtained by bonding together is preferably a fluorinated ethylene group or a fluorinated propylene group.

[0102] In formula (3D), R fd is a hydrocarbyl group having 1 to 40 carbon atoms which may contain a heteroatom. The hydrocarbyl group may be saturated or unsaturated, and may be linear, branched, or cyclic. Specific examples thereof include R 111Examples of the hydrocarbyl group represented by the formula (I) include the same as those exemplified above.

[0103] The synthesis of a sulfonium salt containing an anion represented by formula (3D) is described in detail in JP-A-2010-215608 and JP-A-2014-133723.

[0104] Examples of the anion represented by formula (3D) include the same anions as those exemplified as the anion represented by formula (1D) in JP 2018-197853 A.

[0105] Although the photoacid generator containing the anion represented by formula (3D) does not have a fluorine atom at the α-position of the sulfo group, it has two trifluoromethyl groups at the β-position, and therefore has sufficient acidity to cleave the acid labile group in the base polymer, and can therefore be used as a photoacid generator.

[0106] [(VI) Quencher] The resist material of the present invention may further contain a quencher (VI). When the quencher (VI) is used in the present invention, it is possible to trap the acid generated in the exposed area and suppress diffusion. The quencher (VI) is preferably a weak acid salt consisting of a carboxylate anion and a sulfonium cation having a structure represented by the following formula (4), and may also function as a catalyst to promote the crosslinking reaction of the crosslinking agent (II). [ka]

[0107] The weak acid thus generated in the system does not contribute to the decomposition of the acetal bond formed by the crosslinking agent (II), but rather can function as an acid catalyst that promotes crosslinking of the remaining unreacted vinyl ether structures.

[0108] In formula (4), R 41R is a monovalent organic group which may have a substituent. The organic group may have an ether bond, an ester bond, an amide bond, a lactone ring, or a sultone ring. 41 Preferably, the alkyl group contains an aromatic hydrocarbon group, and more preferably, the alkyl group contains an iodine atom.

[0109] In formula (4), R 42 ~R 44 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may contain a heteroatom. 42 , R 43 and R 44 Any two of may be bonded to each other to form a ring together with the sulfur atom to which they are attached.

[0110] Examples of the anion structure of the quencher (VI) include, but are not limited to, those shown below. [ka]

[0111] [ka]

[0112] [ka]

[0113] [ka]

[0114] Examples of the cation structure of the quencher (VI) include the same as those exemplified as the sulfonium cation in the repeating unit (C) described later.

[0115] The content of the quencher (VI) in the resist material of the present invention is preferably 0.1 to 50 parts by mass, more preferably 1 to 40 parts by mass, based on 100 parts by mass of the base polymer (P). The quencher (VI) may be used alone or in combination of two or more kinds.

[0116] [Surfactants] The resist material of the present invention may contain a surfactant in addition to the above-mentioned components.

[0117] Examples of the surfactant include those described in paragraphs

[0165] to

[0166] of JP 2008-111103 A. The addition of a surfactant can further improve or control the coatability of the resist material. When the resist material of the present invention contains the surfactant, the content is preferably 0.0001 to 10 parts by mass per 100 parts by mass of the base polymer. The surfactant may be used alone or in combination of two or more kinds.

[0118] [Second aspect] The second aspect of the present invention is a resist material containing the above (Ib), (II), (III), and (IV). In the first aspect of the present invention, an additive-type photoacid generator is used as component (V) separately from the base polymer (Ia), whereas in the second aspect of the present invention, the base polymer (Ib) itself has the function of a photoacid generator. Each component will be described in detail below.

[0119] [(Ib) Base polymer] The base polymer (P) in the present invention is a polymer containing a repeating unit (A) containing a hydroxyl group or a carboxyl group, and a repeating unit (C) having a structural site that decomposes upon irradiation with actinic rays or radiation to generate an acid.

[0120] The repeating unit (A) may be the same as that described above in relation to the base polymer (Ia).

[0121] The base polymer contains a repeating unit (C) having a structural portion that decomposes upon exposure to actinic rays or radiation to generate an acid. Since the repeating unit (C) has high polarity, a polymer containing the repeating unit (C) and having a small molecular weight has high solubility in an alkaline developer. On the other hand, when such a readily soluble component is crosslinked to increase its molecular weight, its solubility in the developer is significantly reduced. This effect can greatly change the solubility contrast between the crosslinked and non-crosslinked portions.

[0122] As the repeating unit (C), a repeating unit (C) represented by the following formula (c) can be used. [ka]

[0123] In formula (c), R c1 is a hydrogen atom or a methyl group.

[0124] In formula (c), Z 1 is a single bond or an ester bond. 2 is a single bond or a divalent organic group having 1 to 25 carbon atoms, and may contain one or more of an ester bond, an ether bond, a lactone ring, an amide bond, a sultone ring, and an iodine atom. It may be linear, branched, or cyclic, and specific examples thereof include a methanediyl group, an ethane-1,1-diyl group, an ethane-1,2-diyl group, a propane-1,2-diyl group, a propane-1,3-diyl group, a propane-2,2-diyl group, a butane-1,2-diyl group, a butane-1,3-diyl group, a butane-1,4-diyl group, a butane-2,2-diyl group, a butane-2,3-diyl group, a 2-methylpropane-1,3-diyl group, a pentafluoropropane-1,3-diyl group, a phenyl ... alkanediyl groups having 1 to 20 carbon atoms, such as ethane-1,5-diyl group, hexane-1,6-diyl group, heptane-1,7-diyl group, octane-1,8-diyl group, nonane-1,9-diyl group, and decane-1,10-diyl group; cyclic saturated hydrocarbylene groups having 3 to 20 carbon atoms, such as cyclopentanediyl group, cyclohexanediyl group, norbornanediyl group, and adamantanediyl group; and groups obtained by combining these.

[0125] In formula (c), Rf c1 ~Rf c4 are each independently a hydrogen atom, a fluorine atom, or a trifluoromethyl group, provided that at least one of them is a fluorine atom or a trifluoromethyl group.

[0126] In formula (c), R c2 ~R c4 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may contain a heteroatom.

[0127] Also, R c2 , R c3 and R c4 Any two of the above may be bonded to each other to form a ring together with the sulfur atom to which they are bonded. In this case, the ring is preferably one having the structure shown below. [ka] (In the formula, the dashed line represents R c4 It is a bond with .)

[0128] Examples of the anion structure of the monomer that provides the repeating unit (C) include, but are not limited to, those shown below. [ka]

[0129] [ka]

[0130] [ka]

[0131] [ka]

[0132] [ka]

[0133] [ka]

[0134] [ka]

[0135] [ka]

[0136] [ka]

[0137] [ka]

[0138] [ka]

[0139] [ka]

[0140] [ka]

[0141] [ka]

[0142] Examples of the sulfonium cation of the monomer that provides the repeating unit (C) include, but are not limited to, those shown below. [ka]

[0143] [ka]

[0144] In addition to the repeating units (A) and (C), the base polymer (P) preferably contains a repeating unit (B) in which the hydrogen atom of the carboxyl group in the repeating unit (A) is replaced with an acid labile group. The repeating unit (B) may be the same as that described above for the base polymer (Ia).

[0145] The content of the repeating unit (C) in the base polymer (P) is preferably 50 mol % or less, and more preferably 30 mol % or less and 5 mol % or more.

[0146] [(II) Crosslinking agent] (II) The crosslinking agent may be the same as that described in the first embodiment above.

[0147] [(III) Thermal acid generator] (III) The thermal acid generator may be the same as that described in the first embodiment above.

[0148] [(IV) Organic solvent] (IV) The organic solvent may be the same as that described in the first embodiment above.

[0149] [(V) Components that decompose when exposed to actinic rays or radiation to generate an acid] The resist composition of the second aspect of the present invention may contain an additive-type photoacid generator as component (V), which may be the same as that described in the first aspect above.

[0150] [(VI) Quencher] The resist material according to the second aspect of the present invention may contain a quencher as component (VI), which may be the same as that described above in relation to the first aspect.

[0151] [Surfactants] The resist material of the second aspect of the present invention may contain a surfactant, which may be the same as that described in the first aspect above.

[0152] [Pattern formation method] The resist material of the present invention is suitable as a positive resist material, and when used in the manufacture of various integrated circuits, known lithography techniques can be applied. For example, the pattern formation method includes the following: (i) applying the resist material onto a substrate to form a resist film; (ii) exposing the resist film to high energy radiation; (iii) developing the exposed resist film using a developer. The method includes the steps of:

[0153] [Process (i)] First, the resist material of the present invention is applied to a substrate for integrated circuit manufacturing (Si, SiO2, SiN, SiON, TiN, WSi, BPSG, SOG, organic anti-reflective film, etc.) or a substrate for mask circuit manufacturing (Cr, CrO, CrON, MoSi2, SiO2, etc.) by a suitable coating method such as spin coating, roll coating, flow coating, dip coating, spray coating, doctor coating, etc., so that the coating film has a thickness of 0.01 to 2 μm. This is pre-baked on a hot plate for 30 seconds to 20 minutes to form a resist film. In order to efficiently proceed with the crosslinking reaction by the crosslinking agent, the pre-baking temperature is preferably 130° C. or higher.

[0154] [Step (ii)] Next, the resist film is exposed to high-energy radiation. Examples of the high-energy radiation include ultraviolet radiation, far ultraviolet radiation, EB, EUV radiation with a wavelength of 3 to 15 nm, X-rays, soft X-rays, excimer laser light, gamma rays, synchrotron radiation, etc. When ultraviolet radiation, far ultraviolet radiation, EUV, X-rays, soft X-rays, excimer laser light, gamma rays, synchrotron radiation, etc. are used as the high-energy radiation, the exposure dose is preferably 1 to 200 mJ / cm2, either directly or using a mask for forming a desired pattern. 2 Approximately, more preferably 10 to 100 mJ / cm 2 When EB is used as the high energy beam, the exposure dose is preferably 0.1 to 100 μC / cm 2 Approximately, more preferably 0.5 to 50 μC / cm 2 The positive resist material of the present invention is suitable for fine patterning using high energy rays such as KrF excimer laser light, ArF excimer laser light, EB, EUV, X-rays, soft X-rays, γ-rays, and synchrotron radiation, and is particularly suitable for fine patterning using EB or EUV.

[0155] After the exposure, PEB (post-exposure bake) may be performed on a hot plate or in an oven, preferably at 50 to 150° C. for 10 seconds to 30 minutes, more preferably at 60 to 120° C. for 30 seconds to 20 minutes. PEB is a heating step performed after the exposure of the resist film.

[0156] [Step (iii)] After exposure or PEB, the exposed resist film is developed using a developer of an alkaline aqueous solution of 0.1 to 10 mass %, preferably 2 to 5 mass %, such as tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), or the like, for 3 seconds to 3 minutes, preferably 5 seconds to 2 minutes, by a conventional method such as a dip method, a puddle method, a spray method, or the like. The portions irradiated with light are dissolved in the developer, while the unexposed portions are not dissolved, and the desired positive pattern is formed on the substrate.

[0157] The resist material can also be used for development by organic solvent development.The developer used in this case includes 2-octanone, 2-nonanone, 2-heptanone, 3-heptanone, 4-heptanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methylcyclohexanone, acetophenone, methylacetophenone, propyl acetate, butyl acetate, isobutyl acetate, pentyl acetate, butenyl acetate, isopentyl acetate, propyl formate, butyl formate, isobutyl formate, pentyl formate, isopentyl formate, methyl valerate, methyl pentenoate, methyl crotonate, ethyl crotonate, Examples of the organic solvent include methyl propionate, ethyl propionate, ethyl 3-ethoxypropionate, methyl lactate, ethyl lactate, propyl lactate, butyl lactate, isobutyl lactate, pentyl lactate, isopentyl lactate, methyl 2-hydroxyisobutyrate, ethyl 2-hydroxyisobutyrate, methyl benzoate, ethyl benzoate, phenyl acetate, benzyl acetate, methyl phenylacetate, benzyl formate, phenylethyl formate, methyl 3-phenylpropionate, benzyl propionate, ethyl phenylacetate, 2-phenylethyl acetate, etc. These organic solvents can be used alone or in combination of two or more.

[0158] At the end of the development, rinsing is performed. As the rinsing liquid, a solvent that is miscible with the developer and does not dissolve the resist film is preferable. As such a solvent, alcohols having 3 to 10 carbon atoms, ether compounds having 8 to 12 carbon atoms, alkanes, alkenes, alkynes, and aromatic solvents having 6 to 12 carbon atoms are preferably used.

[0159] Specific examples of alcohols having 3 to 10 carbon atoms include n-propyl alcohol, isopropyl alcohol, 1-butyl alcohol, 2-butyl alcohol, isobutyl alcohol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, tert-pentyl alcohol, neopentyl alcohol, 2-methyl-1-butanol, 3-methyl-1-butanol, 3-methyl-3-pentanol, cyclopentanol, 1-hexanol, 2-hexanol, and 3-hexanol. , 2,3-dimethyl-2-butanol, 3,3-dimethyl-1-butanol, 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-1-pentanol, 3-methyl-2-pentanol, 3-methyl-3-pentanol, 4-methyl-1-pentanol, 4-methyl-2-pentanol, 4-methyl-3-pentanol, cyclohexanol, and 1-octanol.

[0160] Examples of the ether compound having 8 to 12 carbon atoms include di-n-butyl ether, diisobutyl ether, di-sec-butyl ether, di-n-pentyl ether, diisopentyl ether, di-sec-pentyl ether, di-tert-pentyl ether, and di-n-hexyl ether.

[0161] Examples of alkanes having 6 to 12 carbon atoms include hexane, heptane, octane, nonane, decane, undecane, dodecane, methylcyclopentane, dimethylcyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, cycloheptane, cyclooctane, cyclononane, etc. Examples of alkenes having 6 to 12 carbon atoms include hexene, heptene, octene, cyclohexene, methylcyclohexene, dimethylcyclohexene, cycloheptene, cyclooctene, etc. Examples of alkynes having 6 to 12 carbon atoms include hexine, heptine, octyne, etc.

[0162] Examples of aromatic solvents include toluene, xylene, ethylbenzene, isopropylbenzene, tert-butylbenzene, and mesitylene.

[0163] Rinsing can reduce the occurrence of resist pattern collapse and defects. Rinsing is not always necessary, and not performing rinsing can reduce the amount of solvent used.

[0164] The developed hole pattern or trench pattern can also be shrunk by thermal flow, RELACS technology, or DSA technology. A shrink agent is applied onto the hole pattern, and the shrink agent crosslinks on the surface of the resist film due to the diffusion of an acid catalyst from the resist film during baking, and the shrink agent adheres to the sidewalls of the hole pattern. The baking temperature is preferably 70 to 180°C, more preferably 80 to 170°C, and the baking time is preferably 10 to 300 seconds, and excess shrink agent is removed to reduce the hole pattern. EXAMPLES

[0165] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.

[0166] [Preparation and evaluation of resist materials] (1) Preparation of resist material The components were dissolved in a solvent containing 50 ppm of OmNova's PolyFox PF-636 surfactant, and the solutions were filtered through a 0.2 μm filter to prepare resist materials (Examples: R1 to R17, Comparative Examples: cR1 to cR13). The details of each resist material are shown in Tables 1 and 2.

[0167] The contents of each component in Tables 1 and 2 are as follows: Organic solvent: PGMEA (propylene glycol monomethyl ether acetate) DAA (Diacetone Alcohol) EL (Ethyl lactate)

[0168] Base polymer: P-1~P-11, cP-1, cP-2 [ka]

[0169] [ka]

[0170] Photoacid generator: PAG-1~PAG-5 [ka]

[0171] Quencher: Q-1~Q-5 [ka]

[0172] Crosslinking agents: X-1, X-2, X-3, X-4 [ka]

[0173] Thermal acid generators: T-1 to T-7, cT-1 to cT-5 [ka]

[0174] [ka]

[0175] Other additives: A-1, A-2, A-3, A-4 [ka]

[0176] [Table 1]

[0177] [Table 2]

[0178] (2) Crosslinking Reactivity Evaluation (Examples 1-1 to 1-19, Comparative Examples 1-1 to 1-13) Resist materials R1 to R17 and cR1 to 13 were spin-coated on a Si substrate and pre-baked for 60 seconds using a hot plate to form a resist film with a thickness of 50 nm. This was peeled off from the substrate and dissolved in an organic solvent, and the weight average molecular weight in terms of polystyrene was measured by gel permeation chromatography (GPC) using dimethylformamide as the solvent. Table 3 shows the pre-baking temperature and the molecular weight after pre-baking when the resist films of Examples 1-1 to 1-19 were formed. The above contents of Comparative Examples 1-1 to 1-13 are shown in Table 4.

[0179] (3) Dissolution contrast evaluation (Examples 2-1 to 2-19, Comparative Examples 2-1 to 2-9) Resist materials R1 to R17 and cR5 to cR13 were spin-coated on an anti-reflective film DUV-42 manufactured by Nissan Chemical Co., Ltd., which was prepared on an 8-inch wafer with a thickness of 61 nm, and pre-baked using a hot plate for 60 seconds to prepare a resist film with a thickness of 50 nm. This was exposed using a KrF exposure machine (manufactured by Nikon Corporation; S206D), subjected to PEB at 95°C for 60 seconds on a hot plate, and developed with a 2.38 mass% TMAH aqueous solution for 30 seconds. The resist film thickness after this development process was measured, and the relationship between the exposure dose and the resist film thickness after development process was plotted to analyze the dissolution contrast. Furthermore, the contrast was evaluated according to the following criteria, and the results were used as Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-9. In addition, a thickness gauge manufactured by Hitachi High-Tech Corporation was used to measure the film thickness. total VM-2210 was used. The results of Examples 2-1 to 2-19 are shown in Table 5, and those of Comparative Examples 2-1 to 2-9 are shown in Table 6.

[0180] As representative compositions in the above dissolution contrast evaluation, the contrast curves of the resist films of Example 2-9 and Comparative Example 2-2 are shown in FIG. 1. The vertical axis in FIG. 1 is the film thickness after development normalized by the film thickness before development. The contrast values ​​in Table 5 represent the slope of the film thickness change with respect to the exposure dose at the point where the solubility of the resist film in the developer changes rapidly. In the section from when the film thickness becomes 80% or less of the initial film thickness to when the film is completely dissolved, the horizontal axis is the logarithm of the exposure dose, and the vertical axis is the slope of the normalized film thickness, which is the contrast value. The contrast of the resist film formed from each resist composition was evaluated as follows based on the absolute value of the contrast value. (Judgment criteria) ◎: Absolute contrast value is 10 or more ○: Absolute contrast value is 5 or more and less than 10 ×: Absolute contrast value is less than 5

[0181] (4) Storage stability evaluation (Examples 3-1 to 3-17, Comparative Examples 3-1 to 3-4) The resist materials shown in Tables 1 and 2 were stored at 40°C and 23°C for 2 weeks, and then spin-coated on an anti-reflective film DUV-42 manufactured by Nissan Chemical Co., Ltd., which was prepared on an 8-inch wafer with a thickness of 61 nm, and pre-baked for 60 seconds using a hot plate to prepare a resist film with a thickness of approximately 50 nm. A film thickness meter VM-2210 manufactured by Hitachi High-Technologies Corporation was used to measure the film thickness. This was exposed using a KrF exposure machine (Nikon Corporation; S206D, NA 0.68, σ 0.75, 2 / 3 ring illumination, 6% halftone phase shift), and PEB was performed on a hot plate at 95°C for 60 seconds, and development was performed with a 2.38 mass% TMAH aqueous solution for 30 seconds. The developed pattern was observed with a length measuring SEM (S9380) manufactured by Hitachi High-Technologies Corporation, and the sensitivity was evaluated. The difference in sensitivity when the 40°C stored product and the 23°C stored product were evaluated under the same conditions was evaluated according to the following criteria. The results of Examples 3-1 to 3-17 are shown in Table 7, and the results of Comparative Examples 3-1 to 3-4 are shown in Table 8. (Judgment criteria) ○: Sensitivity difference is less than 2% ×: Sensitivity difference is 2% or more

[0182] (5) Lithography Evaluation (Examples 4-1 to 4-17, Comparative Examples 4-1 to 4-9) Resist materials R1 to R17 and cR5 to cR13 shown in Tables 1 and 2 were spin-coated on an anti-reflective film DUV-42 manufactured by Nissan Chemical Co., Ltd., which was prepared on an 8-inch wafer with a thickness of 61 nm, and pre-baked for 60 seconds using a hot plate to prepare a resist film with a thickness of approximately 50 nm. This was exposed using an electron beam lithography system (ELS-F125, accelerating voltage 125 kV) manufactured by Elionix, and PEB was performed on a hot plate at 95°C for 60 seconds, and development was performed with a 2.38 mass% TMAH aqueous solution for 30 seconds. The developed pattern was observed with a length measuring SEM (S9380) manufactured by Hitachi High-Technologies Corporation, and the standard deviation (σ) calculated from the results was tripled (3σ) to obtain the pattern width variation (LWR). Furthermore, the pattern width variation was evaluated based on the following criteria. The results of Examples 4-1 to 4-17 are shown in Table 9, and the results of Comparative Examples 4-1 to 4-9 are shown in Table 10. (Judgment criteria) ◎: LWR value is less than 3.0 〇: LWR value is 3.0 or more and less than 3.5 ×: LWR value is 3.5 or more

[0183] [Table 3]

[0184] [Table 4]

[0185] [Table 5]

[0186] [Table 6]

[0187] [Table 7]

[0188] [Table 8]

[0189] [Table 9]

[0190] [Table 10]

[0191] As shown in Tables 3 and 4, in Examples 1-1 to 1-19 containing a vinyl ether crosslinking agent and a thermal acid generator, the average molecular weight after prebaking increased, suggesting that the crosslinking reaction had progressed. In Example 1-11, it was found that the resist film after prebaking was crosslinked to such an extent that it was insoluble in a GPC solvent. On the other hand, when a thermal acid generator of sulfonic acid or sulfonate type, or carboxylate type not containing a fluorine atom was added, no molecular weight increase effect was observed. When the acidity of the acid generated by the thermal acid generator was too weak, it did not function as a crosslinking catalyst, and when the acidity was too strong, it was suggested that the decomposition reaction of the acetal bond occurred immediately after crosslinking, and it was found that control of the acidity of the generated acid is important.

[0192] As shown in FIG. 1, it can be confirmed that the difference in solubility between the exposed and unexposed parts is significantly different in Example 2-9 compared to Comparative Example 2-2, and the film thickness change after development processing with respect to the amount of exposure is steep. The contrast values ​​in Tables 5 and 6 represent the slope of this film thickness change, with a positive slope for negative resists and a negative slope for positive resists. Also, the larger the absolute value, the better the dissolution contrast. All of Example Groups 2-1 to 2-19, which contain a polymer having a reactive group, a crosslinking agent, and a fluorocarboxylate-type thermal acid generator, showed good contrast, which is believed to be due to the promotion of crosslinking of the unexposed parts by the thermal acid generator. It was also revealed that resists containing vinyl ethers with more crosslinking sites showed good contrast. In addition, resist compositions containing a structural unit (C) that generates acid by light in the base polymer showed particularly excellent contrast. Since the structural unit (C) has high polarity and hydrophilicity, uncrosslinked low molecular weight materials containing (C) have high solubility in the developer. On the other hand, when such a soluble component is crosslinked to increase its molecular weight, its solubility in the developer is significantly reduced. Because of this effect, the solubility contrast between the exposed and unexposed areas can be significantly changed, and therefore it is preferable that the base polymer has the structural unit (C).

[0193] The resist films using resist compositions cR1-cR4, which do not contain a thermal acid generator and to which trace amounts of acids A-1-A-4 are added as crosslinking accelerators, became thicker during long-term storage, and the sensitivity difference value also increased, resulting in lower sensitivity, as shown in Comparative Examples 3-1-3-4 in Table 8. This is thought to be due to the fact that Comparative Examples 3-1-3-4 contain acids as crosslinking accelerators, and therefore the crosslinking reaction proceeds during storage as a solution, resulting in the polymer becoming high molecular weight. Therefore, it was shown that resist materials that do not contain a thermal acid generator have poor storage stability, even if they have the structural unit (C).

[0194] As shown in Table 9, all of Examples 4-1 to 4-17, which contained a polymer having a reactive group, a crosslinking agent, and a fluorocarboxylate-type thermal acid generator, showed good LWR. In addition, the resist composition having a structural unit (C) that generates acid by light in the base polymer showed particularly excellent LWR.

[0195] The above results demonstrate that the resist material of the present invention has high dissolution contrast and good LWR, and therefore has small edge roughness and dimensional variation, excellent resolution, good pattern shape after exposure, and good storage stability.

[0196] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. A resist material comprising: (Ia) a polymer containing a repeating unit (A) containing a hydroxyl group or a carboxy group; (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; (V) a component that decomposes when irradiated with actinic rays or radiation to generate an acid; and A resist material comprising: 【Chemistry 1】 In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group, and n is an integer from 1 to 4. 【Chemistry 2】 [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of these may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

2. A resist material comprising: (Ib) a polymer containing a repeating unit (A) having a hydroxyl group or a carboxyl group, and a repeating unit (C) having a structural moiety that is decomposed upon exposure to actinic rays or radiation to generate an acid, (II) a crosslinking agent having a structure represented by the following formula (1): (III) a thermal acid generator having a structure represented by the following formula (2): (IV) an organic solvent; A resist material comprising: 【Chemistry 3】 In the formula, R represents an organic group having a valence of n which may have a substituent. L 1 is a linking group selected from a single bond, an ester bond, and an ether bond. R 1 is a single bond or a divalent organic group, and n is an integer from 1 to 4. 【Chemistry 4】 [In the formula, R 31 R is a monovalent organic group which may have a heteroatom or a substituent. 32 ~R 34 are each independently a monovalent hydrocarbon group having 1 to 15 carbon atoms which may contain a heteroatom. 32 , R 33 and R 34 Any two of these may be bonded to each other to form a ring together with the nitrogen atom to which they are attached.

3. The resist material according to claim 2 , wherein the repeating unit (C) contained in the polymer is represented by the following formula (c): 【Chemistry 5】 [In the formula, R c1 is a hydrogen atom or a methyl group. Z 1 is a single bond or an ester bond. 2 is a single bond or a divalent organic group having 1 to 25 carbon atoms, and may contain one or more of an ester bond, an ether bond, a lactone ring, an amide bond, a sultone ring, and an iodine atom. Rf c1 ~Rf c4 are each independently a hydrogen atom, a fluorine atom or a trifluoromethyl group, provided that at least one of them is a fluorine atom or a trifluoromethyl group. R c2 ~R c4 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may contain a heteroatom; R c2 , R c3 and R c4 Any two of these may be bonded to each other to form a ring together with the sulfur atom to which they are attached.

4. 4. The resist material according to claim 2, further comprising (V) a component that decomposes upon irradiation with actinic rays or radiation to generate an acid.

5. The resist material according to claim 1 , wherein the repeating unit (A) contained in the polymer is represented by the following formula (a1) and / or (a2): 【Chemistry 6】 [In the formula, R A Each of Y is independently a hydrogen atom or a methyl group. a1 Y each independently represents a single bond or a divalent linking group having 1 to 15 carbon atoms and at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom. a2 R are each independently a single bond or a divalent linking group having 1 to 12 carbon atoms and at least one of a phenylene group, a naphthylene group, an ester bond, an ether bond, a lactone ring, an amide group, and a hetero atom. a1 is a hydrogen atom, a fluorine atom, or an alkyl group; R a1 and Y a2 may be bonded to form a ring. k is 1 or 2, l is an integer of 0 to 4, and 1≦k+l≦5. m is 0 or 1.]

6. R in the formula (2) 31 The resist material according to claim 1 , further comprising an iodine atom.

7. 7. The resist material according to claim 1, wherein R in the formula (1) contains an aromatic hydrocarbon group.

8. The resist material according to claim 1 , further comprising: (VI) a quencher.

9. A pattern formation method comprising the steps of: (i) applying the resist material according to any one of claims 1 to 8 onto a substrate to form a resist film; (ii) exposing the resist film to high energy radiation; (iii) developing the exposed resist film using a developer; A pattern forming method comprising the steps of:

10. 10. The pattern formation method according to claim 9, further comprising a step of pre-baking the resist film at 130[deg.] C. or higher in the step (i).

Citation Information

Patent Citations

  • JP187326A

  • Electron microscope focussing driving display unit

    JP1980062651A

  • Ink for inkjet, color filter and method for producing the same, and liquid crystal display and image display device using the same

    JP2010018788A

  • Resist composition and salt

    JP2013200561A

  • Acid-labile hyperbranched copolymer and associated photoresist composition and method of forming electronic device

    JP2017110191A